Investigating Chemical Composition and Functionality of Lactobacillus acidophilus LA-5 Postbiotics Prepared in Classic and Cheese Whey Media - Nasri, Fatemeh; Alizadeh, Arash; Incili, Goekhan Kuersad; Hayaloglu, Ali Adnan; Moradi, Mehran (Springer, 2025)
This study aimed to characterize two types of postbiotics from Lactobacillus acidophilus LA-5 prepared in De Man, Rogosa, and Sharpe (MRS-Pb) and UF cheese whey (W-Pb). We compared the chemical compositions, functional properties, and toxicities of the prepared probiotics. Assessments included antimicrobial and antioxidant activities, total and individual phenolic compounds, volatile compounds, individual free amino acids, and organic acid contents. Cytotoxicity and potential effects on cell proliferation were assessed using MTT and wound healing assays in HCT-116 intestinal epithelial cancer cells. The results revealed differences in the chemical composition of the two postbiotics. Citric, lactic, and butyric acids were the main organic acids in W-Pb, whereas malic and acetic acids were the main organic acids in MRS-Pb. High levels of hydrocarbons were found in MRS-Pb. W-Pb exhibited potent antimicrobial activity against Listeria monocytogenes and Escherichia coli than MRS-Pb, while the antioxidant potential of MRS-Pb was higher than that of W-Pb. L. acidophilus postbiotics significantly reduced HCT-116 cell viability in a dose-dependent manner (10, 20, and 40 mg/mL for MRS-Pb and 10 and 20 mg/mL for W-Pb). MRS-Pb exhibited more potent effects and cytotoxicity than W-Pb did. Postbiotics did not affect HCT-116 cell proliferation or migration. Both postbiotics increased TAC in a concentration-dependent manner in treated cells, with MRS-Pb showing a stronger effect. These results suggest that the type of culture medium can significantly affect the bioactive properties, chemical composition, and toxicity of postbiotics.
Keywords: Cell-free supernatant; Parabiotics; Lactic acid bacteria; Probiotics; Colon cancer; UF cheese whey